REVISION OF THE GENUS CHRYSOCORIS HAHN (HEMIPTERA: SCUTELLERIDAE) FROM INDIA - S. PARVEEN,; V. V. RAMAMURTHY,; K. USMANI,; S. KHOKHAR, (The Bioscan, 2013)
Genus Chrysocoris is one of the largest groups of Scutelleridae and it is represented by 21 species from the Oriental Region. This study includes nine species i.e. C. andamanensis, C. dilaticollis, C. fascialis, C. marginellus, C. patricius, C. pulchellus, C. purpureus, C. stockerus and C. stollii of the fourteen species from India, and therefore redescribed. The illustrations of the salient distinguishing characters including the thoracic scent efferent system and the genitalia are the highlights of the study.